2001
DOI: 10.1021/ja002177z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Transfer to Carbonyls and Imines from a Hydroxycyclopentadienyl Ruthenium Hydride:  Evidence for Concerted Hydride and Proton Transfer

Abstract: Reaction of ([2,5-Ph(2)-3,4-Tol(2)(eta(5)-C(4)CO)](2)H)Ru(2)(CO)(4)(mu-H) (6) with H(2) formed [2,5-Ph(2)-3,4-Tol(2)(eta(5)-C(4)COH)Ru(CO)(2)H] (8), the active species in catalytic carbonyl reductions developed by Shvo. Kinetic studies of the reduction of PhCHO by 8 in THF at -10 degrees C showed second-order kinetics with Delta H(double dagger) = 12.0 kcal mol(-1) and Delta S(double dagger) = -28 eu. The rate of reduction was not accelerated by CF(3)CO(2)H, and was not inhibited by CO. Selective deuteration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
304
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(332 citation statements)
references
References 41 publications
20
304
1
7
Order By: Relevance
“…They showed that the transfer of hydrogens may take place in a concerted fashion or it may involve two separate hydrogen transfer steps with approximately equal barriers, and that these processes can be distinguished. 25 For a concerted reaction in which both hydrogens are transferred in a single step, the kinetic isotope effect for the doubly labeled material should be equal to the product of the two individual isotope effects. In our case, KIE CHOH/CHOD * KIE CHOH/CDOH = 5.95 (sd=1.7), which is appreciably larger than the experimentally observed KIE CHOH/CDOD of 3.60.…”
Section: Isotopic Labeling Of the Hydrogen Donormentioning
confidence: 99%
“…They showed that the transfer of hydrogens may take place in a concerted fashion or it may involve two separate hydrogen transfer steps with approximately equal barriers, and that these processes can be distinguished. 25 For a concerted reaction in which both hydrogens are transferred in a single step, the kinetic isotope effect for the doubly labeled material should be equal to the product of the two individual isotope effects. In our case, KIE CHOH/CHOD * KIE CHOH/CDOH = 5.95 (sd=1.7), which is appreciably larger than the experimentally observed KIE CHOH/CDOD of 3.60.…”
Section: Isotopic Labeling Of the Hydrogen Donormentioning
confidence: 99%
“…The deuterated substrates 1,2-butanediol-d2 and 2,2',6,6'-cyclohexanone-d4 were prepared by previously reported procedures [12,13]. The Casey-Shvo catalyst (1) [10] and the Rh(dppp)2Cl catalyst (2, dppp = 1,3-bis(diphenylphosphino)propane) [14] were synthesized according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has shown 3 that the Casey/Shvo catalyst achieves higher dehydrogenation rates with primary alcohols than with secondary alcohols [10], thus, it seems likely that the major product of the dehydrogenation reactions will be an α-hydroxyaldehyde (α-HA), formed by dehydrogenation at the primary alcohol (eq. 1) [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations